Multifunctional Nutrient-Binding Proteins Adapt Human Symbiotic Bacteria for Glycan Competition in the Gut by Separately Promoting Enhanced Sensing and Catalysis - Elizabeth A. Cameron (American Society for Microbiology, 2014)
ABSTRACT To compete for the dynamic stream of nutrients flowing into their ecosystem, colonic bacteria must respond rapidly to new resources and then catabolize them efficiently once they are detected. The Bacteroides thetaiotaomicron starch utilization system (Sus) is a model for nutrient acquisition by symbiotic gut bacteria, which harbor thousands of related Sus-like systems. Structural investigation of the four Sus outer membrane proteins (SusD, -E, -F, and -G) revealed that they contain a total of eight starch-binding sites that we demonstrated, using genetic and biochemical approaches, to play distinct roles in starch metabolism in vitro and in vivo in gnotobiotic mice. SusD, whose homologs are abundant in the human microbiome, is critical for the initial sensing of available starch, allowing sus transcriptional activation at much lower concentrations than without this function. In contrast, seven additional binding sites across SusE, -F, and -G are dispensable for sus activation. However, they optimize the rate of growth on starch in a manner dependent on the expression of the bacterial polysaccharide capsule, suggesting that they have evolved to offset the diffusion barrier created by this structure. These findings demonstrate how proteins with similar biochemical behavior can serve orthogonal functions during different stages of cellular adaptation to nutrients. Finally, we demonstrated in gnotobiotic mice fed a starch-rich diet that the Sus binding sites confer a competitive advantage to B. thetaiotaomicron in vivo in a manner that is dependent on other colonizing microbes. This study reveals how numerically dominant families of carbohydrate-binding proteins in the human microbiome fulfill separate and sometimes cooperative roles to optimize gut commensal bacteria for nutrient acquisition. IMPORTANCE Our intestinal tract harbors trillions of symbiotic microbes. A critical function contributed by this microbial community is the ability to degrade most of the complex carbohydrates in our diet, which not only change from meal to meal but also cannot be digested by our own bodies. A numerically abundant group of gut bacteria called the Bacteroidetes plays a prominent role in carbohydrate digestion in humans and other animals. Currently, the mechanisms that allow this bacterial group to rapidly respond to available carbohydrates and then digest them efficiently are unclear. Here, we present novel functions for four carbohydrate-binding proteins present in one member of the Bacteroidetes, revealing that these proteins serve unique and separable roles in either initial nutrient sensing or subsequent digestion. Because the protein families investigated are numerous in other gut bacteria colonizing nearly all humans and animals, our findings are fundamentally important to understanding how symbiotic microbes assist human digestion.